Social studies students’ awareness and knowledge-of sexuality education in Abeokuta: implications for 2030 education agenda (2019)
The study examined social studies students' awareness and knowledge of sexuality education in public junior secondary schools in Abeokuta North Local Government Area of Ogun State. The design for the study was a descriptive survey type. The population of the study was all social studies students in public secondary schools in Abeokuta North Local Government Area of Ogun State. Five (5) public junior secondary schools were selected in the study area through random sampling. 90 JSS3 students were purposively selected from each school because they had been exposed to the concept of sexuality through social studies and were more mature. A total of444 respondents (155 males and 289 females) participated in the study. The instruments used were Students’ Awareness of Sexuality Education Questionnaire (0.87) and Students’ perception of Sexuality Education Questionnaire (0.83). Two research questions were raised and answered. Data collected were analysed using the descriptive statistics of mean, standard deviation, frequency count and simple percentage. The findings revealed that public secondary school students were moderately aware of sexuality education, and that they possessed an average level of knowledge of sexuality education. Based on these findings, it was recommended that new strategies and topics on sexuality education be included in the social studies curriculum by the state and federal ministries of education. Also, that, governments and non-governmental organizations should organise public enlightenment campaigns to further strengthen sexuality education programmes to correct misconceptions about it.